P105 Women with greater post-traumatic stress symptom severity and less disrupted sleep have improved fear extinction recall compared to men. (9th November 2022) - Schenker, M; Ince, S; Ney, L; Hsu, C; Zuj, D; Jordan, A; Nicholas, C; Felmingham, K
Abstract: Sleep has been found to play a key role in fear conditioning, extinction learning and extinction recall, the paradigm modelling the development, maintenance and treatment of anxiety disorders including post-traumatic stress disorder (PTSD), which are disorders commonly associated with sleep disturbances. Previous studies examining associations between sleep and fear or extinction processes predominately focused on objectively measured sleep architecture using polysomnography, and the majority of the research has been done in healthy populations. To date, little research has focused on subjective sleep measures and particularly in clinical populations including PTSD, which often experience subjectively poor sleep. Here we investigated whether subjective sleep disturbance, sleep onset latency, wake after sleep onset or sleep efficiency were related to fear conditioning, extinction learning or extinction recall in a large sample of individuals with a range of PTSD symptom severity and healthy controls. Overall, we did not find that sleep was associated with fear conditioning extinction learning or extinction recall. However, emerging evidence highlighting the critical role of sex in PTSD risk, fear conditioning processes, as well as in the sleep-fear conditioning relationship. Exploratory analyses examining sex-specific effects found that shorter sleep onset latency and greater sleep efficiency during the previous night were associated with improved extinction recall in women with higher PTSD symptom severity. This suggests that less time falling asleep and longer time asleep while in bed may be protective against the commonly observed impaired extinction recall in PTSD in highly symptomatic women, but is not relevant in men.